Agricultural Marketing : Structural Models for Price Analysis. - Vercammen, James (Taylor & Francis, 2011)
The price of food has become very volatile in recent years for a variety of reasons, including a strengthened connection between the prices of agricultural commodities and other commodities such as oil and metals, more volatile production due to more frequent droughts and floods, and a rising demand for biofuels. Understanding the determinants of agricultural commodity prices and the connections between prices has become a high priority for academics and applied economists who are interested in agricultural marketing and trade, policy analysis and international rural development. This book buil.